Developing Instructional Videos on Indonesia's Cultural Diversity Based on Merauke Wisdom - Remma Ranggitia; Fredy Fredy; Karlina Wog Lieung (CV. Dharma Samakta Edukhatulistiwa, 2025)
The use of creative and innovative teaching materials in elementary schools is limited, especially in integrating local wisdom from Merauke. This research aims to develop a learning video based on Merauke's local wisdom that is suitable for use in schools. Using a Research and Development (R&D) approach with the ADDIE model, adapted into three stages: analysis, design, and development, the study involved lecturers' assessments and teacher and student questionnaires. Conducted at SD Yapis II, Merauke, the results show the video received 82.5% for the media aspect and 95% for the material aspect, both categorized as very feasible. Teacher and student responses were 90% and 91.89%, respectively, both rated as very interesting. The product is deemed highly suitable for use.